2009
DOI: 10.1002/ar.20882
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of the Human Embryonic Brain During Rapid Growth: Area Analysis

Abstract: This report focuses on growth of the brain of the early human embryo, Carnegie stages 12-23. Areas of median sections from 50 to 58 embryos were measured to determine the best mathematical model to describe growth of the three primary brain vesicles and to determine the change in the ratio of tissue to cavity areas (T/C). An exponential model best describes growth of the brain and head during this time period. The head expands 248-fold compared with a 171-fold growth of the brain. The whole brain, forebrain, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…Levitan and Desmond (2009) previously noted that an increase in the volumes of the brain cavities is a feature of the embryonic period. The cavity volume was relatively large, but there was no exponential increase in cavity volume, despite the complicated changes that the cavity underwent in the late embryonic stages in our study.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Levitan and Desmond (2009) previously noted that an increase in the volumes of the brain cavities is a feature of the embryonic period. The cavity volume was relatively large, but there was no exponential increase in cavity volume, despite the complicated changes that the cavity underwent in the late embryonic stages in our study.…”
Section: Discussionmentioning
confidence: 96%
“…The present study showed that the morphology of both the brain tissue and cavity of the rhombencephalon was affected by the development of the pons and medulla of the brain stem and the cerebellum according to their respective growth time lines. Previous studies have suggested that morphometric changes of the rhombencephalon differ from the other vesicles (Desmond and O'Rahilly, 1981;Levitan and Desmond, 2009). In our study, growth of the brain stem was apparent until CS17, prior to detectable growth of the cerebellum.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Morphometrical studies (both 2D and 3D) can be analyzed using serial histological sections and visualized via 3D modeling and illustrations . However, these methods are laborious and inaccurate.…”
Section: Introductionmentioning
confidence: 99%
“…The neuromeres considered individually, however, were not a part of that study, nor were the complexities of the telencephalon, and the definitions of segments measured are in need of much greater precision. In a subsequent article on areas [Levitan and Desmond, 2009], but based on the 1981 data, mathematical analysis is vitiated by erroneous morphology and incorrect boundaries. It is important to emphasize that revision is necessary for studies of the embryonic period made before the era of systematic, precise graphic reconstructions of the brain at each stage, which began in the 1980s [references in O'Rahilly and Müller, 2006, table 23-2].…”
Section: Introductionmentioning
confidence: 99%